ASPEK YURIDIS PENYEBAB GUGATAN PERCERAIAN YANG DITOLAK DI PENGADILAN AGAMA KETAPANG KELAS II (Studi Kasus Tahun 2020) - Pratiwi, Binti Lailatul; Haliyah, Dahlia; Wibowo, Arif (Al-Usroh, 2022)
This research was conducted to find out: 1) The reasons for the rejected divorce suit at the Ketapang Religious Court; 2) The basic juridical aspect of the judge's consideration in refusing a divorce suit. This research uses jurudical normative with a statute approach and case approach. The data source uses primary data sources in the form of divorce case decisions that were rejected at the Ketapang Religious Court totaling 8 decisions, the Civil Code, Het Herzine Indonesia Reglemen (HIR), Rechtreglement Voor de Buitengwesten (RBG).While secondary data in the form of books, articles, journals and documents related to research. Data collection in this study is by documentation. The data were then analyzed using data reduction, data presentation, and drawing conclusions. The results of this study indicate that: 1) the reason for the rejected divorce suit is because the plaintiff or applicant cannot prove the truth of the argument of his lawsuit, namely the plaintiff or applicant does not present a witness in the trial. As for the witnesses who submitted evidence did not meet the minimum limit and did not know the events that occurred. 2) The panel of judges in deciding the rejected divorce suit in accordance with the applicable laws, namely Law Number 23 of 2006 concerning Population Administration articles 1 paragraphs 7 and 8, Government Regulation No. 9/1975 article 22 paragraph 2 jo. Article 76 paragraph (1) of Law Number 7 of 1989,Rechtreglement Voor de Buitengwesten (RBG)articles 171, 172, 283, 308 and 309, Het Herzine Indonesich Reglemen (HIR) articles 170 and 171, the Civil Code Articles 1905, 1909 and 1911.